A bio metric based approach for using captcha – to enhance accessibility for the visually impaired. - Noorjahan, M. (Disability & Rehabilitation: Assistive Technology, 2020)
Aim: To propose a system for convenience in using CAPTCHA by the Visually Impaired person. Method: To make this access secure CAPTCHA ("Completely Automated Public Turing test to tell Computers and Humans Apart") was invented. This form of CAPTCHA requires that the user type the letters of a distorted image, sometimes with the addition of an obscured sequence of letters or digits that appears on the screen. This traditional method receives many criticism from the disable people. Hence a finger print based CAPTCHA is introduced. Result: A CAPTCHA MONSTER, a convenient system of breaking CAPTCHA for the Visually Impaired is Proposed. Conclusion: Thus in this proposed system, it is possible to access the web services on websites for various day to day applications by effective authentication procedure.